Epigenetic Regulations of Perineural Invasion in Head and Neck Squamous Cell Carcinoma - Pavel Hurník; Pavel Hurník; Zuzana Chyra; Tereza Ševčíková; Jan Štembírek; Jan Štembírek; Kateřina Smešný Trtková; Kateřina Smešný Trtková; Daria A. Gaykalova; Daria A. Gaykalova; Daria A. Gaykalova; Daria A. Gaykalova; et al. (Frontiers in Genetics, 2022)
Carcinomas of the oral cavity and oropharynx belong among the ten most common malignancies in the human population. The prognosis of head and neck squamous cell carcinoma (HNSCC) is determined by the degree of invasiveness of the primary tumor and by the extent of metastatic spread into regional and distant lymph nodes. Moreover, the level of the perineural invasion itself associates with tumor localization, invasion’s extent, and the presence of nodal metastases. Here, we summarize the current knowledge about different aspects of epigenetic changes, which can be associated with HNSCC while focusing on perineural invasion (PNI). We review epigenetic modifications of the genes involved in the PNI process in HNSCC from the omics perspective and specific epigenetic modifications in OSCC or other neurotropic cancers associated with perineural invasion. Moreover, we summarize DNA methylation status of tumor-suppressor genes, methylation and demethylation enzymes and histone post-translational modifications associated with PNI. The influence of other epigenetic factors on the HNSCC incidence and perineural invasion such as tobacco, alcohol and oral microbiome is overviewed and HPV infection is discussed as an epigenetic factor associated with OSCC and related perineural invasion. Understanding epigenetic regulations of axon growth that lead to tumorous spread or uncovering the molecular control of axon interaction with cancer tissue can help to discover new therapeutic targets for these tumors.